Face and Neck Lift—Postoperative Care - Raghavan, Ullas; Daoud, Mahmoud; Ullas, Gautham (Facial Plastic Surgery, 2018)
Primary aim of the article is a discussion of the postoperative care after face and neck lift. A brief history of face and neck lift along with different techniques are described. Importance of preoperative assessment is stressed.
Keywords: facelift; neck lift; postoperative care